Molecular effects of bone marrow derived-Mesenchymal stem cells (BM-MSCs) on some the cytokines encoding-genes in BALB/c mice with systemic lupus erythematosus (SLE) (Eurasian Medical Research Periodical, 2023)
Lupus is a chronic autoimmune disease that occurs due to immune disturbance and poor regulation of the immune response, such as dysfunction of antibodies, immune cell, and cytokines. The study investigates the gene expression of some encoding chemokines and cytokines gene in BALB/c model mice with lupus. Forty male BALB/c mice are divided into four groups; each one consists of ten BALB/c mice. The first groups are injected activated lymphocytes Derivative DNA S/C for induction lupus. The second group was administrated activated lymphocytes Derivative DNA S/C for induction lupus then, treated with bone marrow derived-Mesenchymal stem cells (BM-MSCs); the third group was administered BM-MSCs intravenously only. The control group administrated PBS. After finishing the induction and treatment time, all the animals activated for take the serum for estimation the gene expression of the some of the cytokines and chemokines genes by using RT-PCR techniques in all the study groups. The findings are included that the first group showed significant high expression of IL-6, CCL-5/RANTES, VEGF, ICAM, CCL-2, and IFNγ-encoding genes; and low expression of IL-10 and TGFβ1- encoding gene as compared with the control group. The second group showed a significant low expression of IL-6, CCL-5/RANTES, VEGF, ICAM, CCL-2/MCP-1, and IFNγencoding genes while showing significant high expression of IL-10 and TGFβ1-encoding gene as compared with the control group. The third group doesn't show any changes in the studied cytokines and chemokines gene expression compared to the control group. BM-MSCs can effect on the gene expression of many cytokines and chemokine encoding genes, which treats induced lupus in mice.